A few comments on Nicholas Mystikos’s homily on the sack of Thessalonica by the Arabs in 904 - Gołuchowska, Marta (Balcanica Posnaniensia. Acta et studia, 2011)
The article concerns the homily of Patriarch Nicholas Mystikos delivered after the Arab capture of Thessalonica in 904. The author analyzes the text as a source for research on the Byzantine reaction to one of the most tragic events of the early tenth century. The aim of the article is to determine the function of the homily, the patriarch’s methods of influencing his audience, and the usefulness of the text for reconstructing the events connected with the fall of Thessalonica. The author employs source analysis of the homily and compares it with the account of John Kaminiates and other contemporary testimonies. The study demonstrates that the homily was a direct response to dramatic events and possessed a moral-religious character — the patriarch interpreted the disaster as punishment for the sins of the inhabitants and of Byzantine society as a whole. At the same time, the text contains valuable information about social moods after the capture of the city and about perceptions of the Arab threat. The results of the analysis indicate that the homily of Nicholas Mystikos fulfilled both pastoral and political functions, strengthening the sense of religious community after the catastrophe.